Berry Polyphenols and Fibers Modulate Distinct Microbial Metabolic Functions and Gut Microbiota Enterotype-Like Clustering in Obese Mice - Rodríguez-Daza, Maria-Carolina; Roquim, Marcela; Dudonné, Stéphanie; Pilon, Geneviève; Levy, Emile; Marette, André; Roy, Denis; Desjardins, Yves (Frontiers in Microbiology, 2020)
Berries are rich in polyphenols and plant cell wall polysaccharides (fibers), including cellulose, hemicellulose, arabinans and arabino-xyloglucans rich pectin. Most of polyphenols and fibers are known to be poorly absorbed in the small intestine and reach the colon where they interact with the gut microbiota, conferring health benefits to the host. This study assessed the contribution of polyphenol-rich whole cranberry and blueberry fruit powders (CP and BP), and that of their fibrous fractions (CF and BF) on modulating the gut microbiota, the microbial functional profile and influencing metabolic disorders induced by high-fat high-sucrose (HFHS) diet for 8 weeks. Lean mice-associated taxa, including Akkermansia muciniphila, Dubosiella newyorkensis, and Angelakisella, were selectively induced by diet supplementation with polyphenol-rich CP and BP. Fiber-rich CF also triggered polyphenols-degrading families Coriobacteriaceae and Eggerthellaceae. Diet supplementation with polyphenol-rich CP, but not with its fiber-rich CF, reduced fat mass depots, body weight and energy efficiency in HFHS-fed mice. However, CF reduced liver triglycerides in HFHS-fed mice. Importantly, polyphenol-rich CP-diet normalized microbial functions to a level comparable to that of Chow-fed controls. Using multivariate association modeling, taxa and predicted functions distinguishing an obese phenotype from healthy controls and berry-treated mice were identified. The enterotype-like clustering analysis underlined the link between a long-term diet intake and the functional stratification of the gut microbiota. The supplementation of a HFHS-diet with polyphenol-rich CP drove mice gut microbiota from Firmicutes/Ruminococcus enterotype into an enterotype linked to healthier host status, which is Prevotella/Akkermansiaceae. This study highlights the prebiotic role of polyphenols, and their contribution to the compositional and functional modulation of the gut microbiota, counteracting obesity.